Genome Sequence of an Arthroconidial Yeast, Saprochaete fungicola CBS 625.85 - Brejová, Broňa (Microbiol Resour Announc, 2019)
Saprochaete fungicola is an arthroconidial yeast classified in the Magnusiomyces/Saprochaete clade of the subphylum Saccharomycotina. Here, we report the genome sequence of holotype strain CBS 625.85, assembled to five putative chromosomes. The genome sequence is 20.2 Mbp long and codes for 6,138 predicted proteins.